2020
DOI: 10.1097/ccm.0000000000004738
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Heparin-Binding Protein in Diagnosing Sepsis: A Systematic Review and Meta-Analysis

Abstract: OBJECTIVES: Existing studies evaluating the accuracy of heparin-binding protein for the diagnosis of sepsis have been inconsistent. We conducted a systematic review and meta-analysis to assess the totality of current evidence regarding the utility of heparin-binding protein to diagnose sepsis in patients with presumed systemic infection. DATA SOURCE: PubMed, Embase, the China National Knowledge infrastructure, and WangFang electronic database were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 48 publications
0
35
2
Order By: Relevance
“…Heparin-binding protein (HBP) is also involved in the pathophysiology of severe bacterial infections and may have a role in their management [ 48 ]. A high level of HBP in plasma might be a useful diagnostic marker for detecting organ dysfunction among patients ranging from suspected infections to septic shock [ 49 ]. In clinical studies, high plasma HBP levels in patients with sepsis were associated with a higher early fluid balance, increased organ failure within 5 days, and higher 28-day mortality [ 50 ].…”
Section: Bio-mechanistic Relationship Between Hypoalbuminemia and Infmentioning
confidence: 99%
“…Heparin-binding protein (HBP) is also involved in the pathophysiology of severe bacterial infections and may have a role in their management [ 48 ]. A high level of HBP in plasma might be a useful diagnostic marker for detecting organ dysfunction among patients ranging from suspected infections to septic shock [ 49 ]. In clinical studies, high plasma HBP levels in patients with sepsis were associated with a higher early fluid balance, increased organ failure within 5 days, and higher 28-day mortality [ 50 ].…”
Section: Bio-mechanistic Relationship Between Hypoalbuminemia and Infmentioning
confidence: 99%
“…At present, there is no study on the relationship between HBP in amniotic uid and HCA, but there are many studies on the relationship between HBP and infection, and HBP is considered as a reliable index for predicting severe infection. A meta-analysis of HBP in predicting sepsis in critically ill patients showed that the sensitivity and speci city of HBP in the diagnosis of sepsis were 0.85 and 0.91, respectively [27]; Another study on the relationship between HBP and sepsis also found that it has high diagnostic value. In addition, the study pointed out that the secretory granules secreting HBP were rst mobilized after neutrophil activation, so the rise of HBP was prior to other infection indicators (WBC, C-reactive protein, procalcitonin, lactic acid) [28]; Furthermore, elevated CSF levels of HBP can distinguish patients with acute bacterial meningitis from patients with other central nervous system infections [29].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated HBP level may cause tissue edema, hypotension, and organ dysfunction[4]. In recent years, studies have revealed that HBP is related to the severity of sepsis and can be used as a biomarker[5, 6]. HBP docks on the surface of vascular endothelial cells (ECs) and causes rearrangement of cytoskeleton and vascular leakage through protein kinase C (PKC)[7] and rho kinase signaling pathways[8].…”
Section: Introductionmentioning
confidence: 99%